ANALISIS PENETRALAN AIR ASAM TAMBANG DENGAN METODE AKTIF MENGGUNAKAN POWERBASE DI PIT TIMUR PT DIZAMATRA POWERINDO KABUPATEN LAHAT PROVINSI SUMATERA SELATAN - Lina Rianti; Dendi Ali Akbar Rmadhan Saputra (Jurnal Ilmiah Hospitality, 2022)
Acid mine water refers to water resulted from the oxidation of sulphide mineral from a mining process and exposed to water, and it has high acid level which is indicated by the low value of pH that is below 6. Therefore, acid mine water must be treated so that is does not cause pollution in the area around the mine. In this research, the acid mine water treatment applied active method by using jar test with neutralizer media in from of powerbase. This research only calculated the dosage necessity and cost of powerbase with laboratory scale as well as field scale. The need of powerbase for laboratory scale was 80 kg with the powerbase cost of Rp 752,000.00 for once neutralization/hour. With the cost of Rp 7,520,000.00 the powerbase application with 0.6 gram/1000 ml dosage could increase the pH from 4.3 to 7.62.